ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ðµ â€“ Ñ„Ð°ÐºÑ‚Ð¾Ñ€ Ð¾Ð¿Ñ‚Ð¸Ð¼Ð¸Ð·Ð°Ñ†Ð¸Ð¸ Ñ‚ÐµÑ€Ð°Ð¿ÐµÐ²Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÑÑ„Ñ„ÐµÐºÑ‚Ð° Ð¿Ñ€Ð¾Ð´ÑƒÐºÑ‚Ð¾Ð² ÑÐ¼Ð±Ñ€Ð¸Ð¾Ñ„ÐµÑ‚Ð¾Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ð°Ñ€Ð½Ð¾Ð³Ð¾ ÐºÐ¾Ð¼Ð¿Ð»ÐµÐºÑÐ° (ÐŸÐÐ¤ÐŸÐš) Ð§Ð°ÑÑ‚ÑŒ I. ÐŸÐ°Ñ‚Ð¾Ð»Ð¾Ð³Ð¸Ñ Ð°ÑƒÑ‚Ð¾Ð¸Ð¼Ð¼ÑƒÐ½Ð½Ð¾Ð³Ð¾ Ð³ÐµÐ½ÐµÐ·Ð° ÐºÐ°Ðº Ð¼Ð¾Ð´ÐµÐ»ÑŒ Ð¾Ñ†ÐµÐ½ÐºÐ¸ Ñ‚ÐµÑ€Ð°Ð¿ÐµÐ²Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ ÑÑ„Ñ„ÐµÐºÑ‚Ð° Ð¿Ñ€Ð¸Ð¼ÐµÐ½ÐµÐ½Ð¸Ñ ÐŸÐÐ¤ÐŸÐš - Goltsev, A. N.; Popova, K. N.; Sirous, M. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
The possibility of using model autoimmune diseases for estimating a therapeutic efficiency of cryopreserved products of embryofetoplacental complex (PEFPC) is substantiated. With the example of autoimmune hemolytical anemia there has been shown a multi-profile change of the state of lymphohemopoietic complex of the animals with this pathology. The changes in various links of immune system during pathology development are emphasized. There is noted a possible dependence of their manifestation extent on disorder of harmonic interaction in neuroimmune endocrine block of an organism that stipulates the necessity of treatment of such diseases by preparations with a polyfunctional orientation effect, namely PEFPC.